The Influence of ESG Disclosure and Institutional Ownership on Firm Value with Firm Size as a Moderating Variable (A Case Study of Companies Listed on the Indonesia Stock Exchange in 2018–2024) - Dellagesafhira Sudradjat; Neni Maryani (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This research investigates how environmental, social, and governance (ESG) reporting and the presence of institutional investors impact a company's worth, considering company size as a factor that changes this relationship, based on companies listed on the Indonesian stock market (IDX) between 2018 and 2024. A numerical method was used, analyzing 167 data points after removing unusual values, where the variables were quantified using the GRI standard, the proportion of shares held by institutions, the logarithm of the company's total assets, and Tobin's Q ratio. Regression and moderated regression analysis results indicate that ESG reporting and institutional investors have a noticeably positive influence on a company's worth, accounting for 30.6% of the changes in its value. Company size reduces the impact of ESG reporting but boosts the impact of institutional investors, with the model describing 33.9% of a company's worth. The results highlight the need to improve the quality of ESG practices, increase oversight by institutional investors, and promote more studies into the standards of sustainability reporting.